1975
DOI: 10.1111/j.1476-5381.1975.tb07351.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Vasodilator and Antisecretory Role of Prostaglandins in the Rat Gastric Mucosa by Use of Non‐steroidal Anti‐inflammatory Drugs

Abstract: The effects of non‐steroidal anti‐inflammatory drugs on gastric acid secretion and mucosal blood flow were studied in the rat. Indomethacin, in ulcerogenic doses, caused a dose‐dependent rise in pentagastrin‐stimulated acid secretion, but decreased mucosal blood flow per unit acid secretion. During resting conditions, indomethacin had no significant effect on acid output, but reduced mucosal blood flow. Pretreatment with indomethacin, phenylbutazone or meclofenamate potentiated the secretory response to dibuty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(68 citation statements)
references
References 23 publications
4
64
0
Order By: Relevance
“…The fall in gastric mucosal blood flow induced by indomethacin, in doses sufficient to inhibit postaglandin formation (Vane, 1971) in the mucosa (Main & Whittle, 1975a) could suggest a role for endogenous prostaglandins (or some other product of the prostaglandin cyclo-oxygenase system) in the local regulation of the gastric microcirculation; it has been found that primary prostaglandins of the E and A series for example, can increase resting mucosal blood flow (Main & Whittle, 1973b (Chvasta & Cooke, 1972). Although this could reflect a species difference, a more likely explanation is that such drugs have a topical action, perhaps of a physico-chemical nature, unrelated to inhibition of local prostaglandin synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fall in gastric mucosal blood flow induced by indomethacin, in doses sufficient to inhibit postaglandin formation (Vane, 1971) in the mucosa (Main & Whittle, 1975a) could suggest a role for endogenous prostaglandins (or some other product of the prostaglandin cyclo-oxygenase system) in the local regulation of the gastric microcirculation; it has been found that primary prostaglandins of the E and A series for example, can increase resting mucosal blood flow (Main & Whittle, 1973b (Chvasta & Cooke, 1972). Although this could reflect a species difference, a more likely explanation is that such drugs have a topical action, perhaps of a physico-chemical nature, unrelated to inhibition of local prostaglandin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Erosions, which formed in the glandular mucosa, were counted and each one given a severity rating on a 1-3 scale as previously described (Main & Whittle, 1975a parametric Mann-Whitney U-test, where appropriate. P < 0.05 was taken as significant.…”
Section: Gastric Mucosal Bloodflowmentioning
confidence: 99%
“…The hypothesis that a reduction in MBF and increase in H+ secretion following blockade of endogenous postaglandin formation may under certain conditions contribute to erosion formation (Main & Whittle, 1975;Whittle, 1976) (Chaudhury & Jacobson, 1978) or bicarbonate secretion (Garner & Heylings, 1978), which are essential to the maintenance of mucosal integrity. Various prostaglandins have been shown to be cytoprotective against mucosal lesions caused by Indo and various other damaging agents (Robert, Nezamis, Lancaster & Hanchar, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The stomachs were removed, opened along the greater curvature and rinsed under a stream of water. Erosions formed on the glandular portion of the stomach were observed and each graded on a (0-3) scale based on the length of the ulcer; 0 = normal; 1 = <1mm; 2 = 1-2 mm; 3 = >2 mm (Main and Whittle, 1975). Mean ulcer score for each group was calculated and expressed as the Ulcer Index (UI).…”
Section: Indomethacin Induced Ulcermentioning
confidence: 99%